Inventors and Gatekeepers? The EU Member States and the European External Action Service - Sus, Monika (Journal of Regional Security, 2018)
This project reflects on the ambivalence of the EU member states in their relationships with the new institutional arm of European diplomacy – the European External Action Service, headed by the High Representative. While trapped in rhetorical support for stronger and better-coordinated EU foreign policy, the member states show little willingness to equip the newcomer with political mandate and room for action, and provide a case in point for the post- Maastricht integration paradox. The main aim of this paper is to shed light on the reasons for this paradoxical behaviour. Taking into consideration the timeline 2009−2014, the article looks at patterns and dynamics of the mutual cooperation between the EEAS selected member states (Germany, Poland and the United Kingdom).